Orthogonal cutting mechanisms of CFRP/Ti6Al4V stacks - Xu, Jinyang; El Mansori, Mohamed; Chen, Ming; Ren, Fei (International journal of advanced manufacturing technology, 2019)
The enhanced mechanical/physical properties and improved functionalities have made the carbon fiber–reinforced polymer/titanium alloy (CFRP/Ti6Al4V) stacks very attractive to the modern aerospace industry. However, the current knowledge of machining CFRP/Ti6Al4V stacks remains insufficient to guide their industrial applications. The main contribution of the present paper lies in the scientific understanding of the coupling effects and underlying mechanisms dominating the stack chip formation and cutting response transfer via the orthogonal cutting method. A particular focus was placed on the identification of the impact of different cutting sequence strategies (i.e., cutting from CFRP to Ti6Al4V and from Ti6Al4V to CFRP) on the stack machinability. The orthogonal cutting tests were carefully performed on a shaper machine tool using the polycrystalline diamond (PCD)–tipped inserts. The present study covers a variety of aspects in the CFRP/Ti6Al4V machining including the chip removal process, cutting forces, chip features, bouncing-back phenomenon and machined surface quality. The results discussed in this work allow for a better cutting understanding of CFRP/Ti6Al4V stacks and could advance the state of knowledge of the subject area.